A new species of Acledra s. str. (Hemiptera: Heteroptera: Pentatomidae) from the highlands of Argentina and Bolivia, with a checklist and key to the species of the nominate subgenus - Faúndez, Eduardo I.; Rider, David A.; Carvajal, Máriom A. (Zootaxa, 2014)
Acledra (Acledra) bichromocornis n. sp. from the highlands of Argentina and Bolivia is described. A checklist of the species of Acledra s. str. is provided, including the distribution by country. A key to the species of Acledra s. str. is included.